2018
DOI: 10.1038/s41419-018-0531-z
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic steatosis associated with decreased β-oxidation and mitochondrial function contributes to cell damage in obese mice after thermal injury

Abstract: Severely burned patients who are morbidly obese have poor clinical outcomes with aggravated metabolic consequences, a higher incidence of multiple organ dysfunction/failure, and significantly increased morbidity and mortality. The underlying mechanisms of these adverse outcomes are essentially unknown. Since the liver is one of the central metabolic organs, we hypothesized that thermal injury in obese patients leads to substantially increased lipolysis, hepatic fat infiltration, resulting in profound hepatic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Murine iWAT was fixed, sectioned and imaged at the University of Toronto Microscopy Imaging Laboratory, as described previously [24].…”
Section: Methodsmentioning
confidence: 99%
“…Murine iWAT was fixed, sectioned and imaged at the University of Toronto Microscopy Imaging Laboratory, as described previously [24].…”
Section: Methodsmentioning
confidence: 99%
“…Equally, impaired insulin signaling also affects ER-mitochondria interactions, but here the results are also conflicting. An animal study showed that inhibition of AKT/mTOR signaling led to decreased ER-mitochondria contact in HFD-fed mice (115). In contrast, a greater number of hepatic ERmitochondria contact sites were observed in mice with either nutritionally (HFD) induced or genetically determined obesity compared with their respective lean controls (113).…”
Section: Altered Mam Integrity Induces Insulin Resistance In Periphermentioning
confidence: 99%
“…25 Lipolysis occurs, but suppression of beta oxidation prevents lipid utility for energy and results in hepatic lipidosis. 26 The following burn trauma proteolysis exceeds protein synthesis and leads to skeletal muscle wasting. 6,27 Further increases in energy expenditure in burnassociated hypermetabolism are thought to be mediated by uncoupling protein 1 (UCP1) ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%